2007
DOI: 10.1007/s11096-007-9108-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of inappropriate prescribing in primary care

Abstract: The overall prescribing quality in primary care in Copenhagen County, Denmark is good. However, the majority of patients used one or more medications with inappropriate ratings. The inappropriate prescribing relates to specific therapeutic groups and criteria, which should be targeted in future interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 27 publications
10
51
2
Order By: Relevance
“…In literature are reported dosage errors by 6.7% [7] although the data found in this study is lower than that reported in literature, the consumption of drugs not specified and / or higher than the recommended doses, exposes the EP to the risk of adverse events related to drugs, unwanted physiological responses to exercise, promote drug interactions, adverse reactions and more. Sometimes the EP receives medications for the treatment of acute diseases, but those are included in the prescription and without further review of the evolution of the disease are still prescribed by "repeated formula".…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…In literature are reported dosage errors by 6.7% [7] although the data found in this study is lower than that reported in literature, the consumption of drugs not specified and / or higher than the recommended doses, exposes the EP to the risk of adverse events related to drugs, unwanted physiological responses to exercise, promote drug interactions, adverse reactions and more. Sometimes the EP receives medications for the treatment of acute diseases, but those are included in the prescription and without further review of the evolution of the disease are still prescribed by "repeated formula".…”
Section: Discussioncontrasting
confidence: 67%
“…As evidenced by several studies [5,7,8,12,20,15], consumption of more than 5 medications means a high risk of causing ADR, that added to the result of inappropriate prescribing obtained in this study, half of the population with the methodology STOPP are constantly at risk, because of that, measures must be taken for identification and prevention of PIP. It is proposed to strengthen the integration of clinical services to the pharmaceutical service that also aims to contribute in a harmonious and integral way to improve the quality of individual and collective life under the Health Promotion and Prevention.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This condition corresponds to the characteristic of the subject (71% were female). In contrast, Reis and Cassiani and Carvalho et al and Bregnhøj et al revealed that potential drug interactions occurred in patients with cardiovascular diseases [7,8,13]. Patients with the pathological condition have an increased risk for drug interactions through pharmacokinetic mechanism [2].…”
Section: Discussionmentioning
confidence: 97%
“…Although this is not exceptionally high (Bregnhøj reported prescribing of ineffective medication in 6% of all GP prescriptions 5 ), AVDs may cause serious side effects, like dystonia and parkinsonism. 6,7 Next to this, prescribing ineffective drugs may distract from the preferred approach of non-vestibular dizziness in older patients: a systematic exploration of possible contributory causes of dizziness that are amenable to treatment.…”
Section: Looks Vestibular: Irrational Prescribing Of Antivertiginous mentioning
confidence: 99%